2004
DOI: 10.1002/ejoc.200300671
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyfluorinated Nitrogen‐Containing Heterocycles from Hemifluorinated Enones or Organofluorosilicon Building Blocks as Synthetic Equivalents

Abstract: A series of polyfluorinated heterocycles has been prepared by heterocyclisation of hemifluorinated enones or organofluorosilicon synthetic equivalents with different bis(nucleophiles). These polyfluorinated building blocks were obtained by treatment of acylsilanes with perfluoro organometallic reagents. The method is general and has been applied to aliphatic, aromatic and carbohydrate derivatives, to give oxazolidines, imidazolidines, benzodia‐ and ‐thiazepines, quinolines and pyrimidines bearing both a fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It was therefore concluded that this is a product resulting from one molecule of 365 B reacting with two molecules of 366 b . The NMR spectrum of this compound does not show an AMX signal attributable to the three protons on the seven membered ring but instead gives a signal corresponding to a 2H doublet with a coupling constant of 7 Hz at l. 46 When the reaction of 365 A and 366 a was carried out at reflux temperature, a low melting-point crystalline solid was obtained in addition to a small amount of the expected 367 Aa . The IR spectrum of this compound showed absorption at 1676 cm −1 ; while the band at 1750 cm −1 , which is the typical carbonyl absorption for a -lactam, is not present.…”
Section: Reactions Between 24-disubstitutedmentioning
confidence: 91%
See 3 more Smart Citations
“…It was therefore concluded that this is a product resulting from one molecule of 365 B reacting with two molecules of 366 b . The NMR spectrum of this compound does not show an AMX signal attributable to the three protons on the seven membered ring but instead gives a signal corresponding to a 2H doublet with a coupling constant of 7 Hz at l. 46 When the reaction of 365 A and 366 a was carried out at reflux temperature, a low melting-point crystalline solid was obtained in addition to a small amount of the expected 367 Aa . The IR spectrum of this compound showed absorption at 1676 cm −1 ; while the band at 1750 cm −1 , which is the typical carbonyl absorption for a -lactam, is not present.…”
Section: Reactions Between 24-disubstitutedmentioning
confidence: 91%
“…Condensation of o-aminothiophenol, with the enones 179 (or 180 or 181) provided the corresponding benzothiazepines 182a-c in good yields. In the carbohydrate series, the 1,5-benzothiazepines 182c was obtained as an epimeric mixture (D-xylo/L-arabino in a 85 : 15 ratio), indicating that a further C-4 epimerisation had occurred during the formation of the heterocycle [44][45][46][47] (Scheme 36).…”
Section: Condensation Reactions Of Enones With O-aminothiophenolmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The synthesis of such heterocycles linked to a carbohydrate moiety was also exemplified from carbohydrate-derived acylsilanes. 7,8 In order to form fluorinated homo-C-nucleoside analogues, we performed the synthesis of new compounds bearing an acylsilane function linked to the anomeric carbon atom via a methylene group. This paper is devoted to the account of this synthetic work and to the application of these new carbohydrate derived acylsilanes to the synthesis of fluorinated homo-C-nucleoside analogues.…”
mentioning
confidence: 99%